Efficacy of Sakacin on Selected Food Pathogenic Microorganisms Isolated from Fermented Milk Products - SSD Mohammed; D Damisa; TV Balogu; E Bala (Journal of Applied Sciences and Environmental Management)
The efficacy of sakacin on selected food pathogenic microorganisms isolated from fermented milk products  was investigated. The L .sake was isolated using the pour plate technique and was characterized based on it colony, cell morphology and some biochemical tests. This isolate was identified using standard scheme. The L .sake FCF 33 was propagated in De Man Rogosa Sharpe (MRS) broth for bacteriocin (sakacin) production. The sakacin had inhibitory effects on all test microorganisms (ranging from +5mm to +6mm) except Shigella dysenteriae N11, Salmonella typhimurium N8, Klebsiella ozaenae W24 and Proteus mirabilis N16a). Bacteriocins are antimicrobial substances of lactic acid bacteria (LAB) have gained tremendous attention as potential bio preservatives in the food and dairy industries. The LAB can serve as probiotics, which are products aimed at delivering living, potentially beneficial bacterial cells to the gut ecosystem of humans and other animals. © JASEM